Atrial fibrillation in patients with first-ever stroke: Incidence trends and antithrombotic therapy before the event - Jung, Yo Han; Kim, Young Dae; Kim, Jinkwon; Han, Sang Won; Lee, Kyung-Yul (PloS one, 2018)
Atrial fibrillation (AF) is the most common cardiac arrhythmia among adults. Despite the proven advantages in primary and secondary stroke prevention in patients with AF, oral anticoagulation (OAC) therapy is still underused in many countries. In this study, we investigated the incidence of AF-related ischemic stroke over the past decade in South Korea and trends of preventive antithrombotic therapy use before stroke in a nationwide cohort. The data source for this study was a nationwide sample cohort comprising 1,025,340 individuals that was established by the nationwide health insurance system in 2002. A total of 10,215 patients with acute ischemic stroke (AIS) were selected from the cohort between 2004 and 2013. AF was identified in 1,662 patients, and 979 patients had preexisting AF before AIS. The annual proportion of patients with AIS with AF gradually increased from 13.4% to 22.6% over the study period (p for trends <0.001). Only 14.0% of patients with high risk AF were receiving OAC before the stroke, and this proportion remained relatively constant during the study period. However, the proportion of patients treated with antiplatelet agents had increased from 18.8% in 2004 to 45.3% in 2013, while that of patients receiving no antithrombotic agent decreased from 64.6% in 2004 to 43.9% in 2013. As a limitation, no information was available about non-vitamin K antagonist oral anticoagulants, because they were widely used since late 2014 in Korea. The number of patients with AIS and AF has steadily increased over the last 10 years in Korea. However, a small portion of patients with AF were receiving OAC therapy before the stroke and about half of the patients did not receive any antithrombotic medication. Our study demonstrates that there is huge gap between clinical practice and treatment guidelines for patients with AF in Korea.